An Investigation into Projecting Processes in English and Vietnamese Short Stories and Novels - Nguyễn Thị Xuân Mỹ (2012)
Among the three linguistic metafunctions, the ideational-the metafunction concerned with clauses as representations appears to be the most attractive to the researchers. Each research is of great practical significance. This study …